BMI, socioeconomic status, and bone mineral density in U.S. adults: Mediation analysis in the NHANES - Zhang, Yun; Tan, Caixia; Tan, Wenfu (Frontiers in Nutrition, 2023)
Introduction: The mechanism by which socioeconomic status (SES) affects bone mineral density (BMD) remains unknown, and body mass index (BMI) may be a potential mediator. The purpose of this study was to investigate whether BMI mediates the relationship between SES (education level and Poverty Income Ratio (PIR)) and lumbar BMD and the proportion it mediates. Methods: This study included a total of 11,075 adults from the National Health and Nutrition Examination Survey (NHANES). Lumbar BMD was measured at the lumbar spine by dual-energy x-ray absorptiometry (DXA). Multivariate linear regression and smoothing curve fitting were used to investigate the relationship between SES and lumbar BMD. Mediator analysis was used to investigate the proportion of BMI mediating the association between SES and BMD. Results: In the fully adjusted model, there was a positive correlation between SES and BMD [education level: β=0.025, 95% CI：(0.005, 0.045); PIR: β=0.007, 95% CI：(0.002, 0.011)]. Mediation analysis showed that BMI mediated the relationship between PIR, education level, and lumbar BMD with a range of mediation proportions from 13.33% to 18.20%. Conclusions: BMI partially mediated the positive association between SES and BMD, and this association may be largely mediated by factors other than BMI.